Interactivity Between Phonological Levels in Speech Output: Example From a Child With 3-Methylglutaconic Aciduria Type I. - Little, Danielle; Bernhardt, B. May; Payne, Elizabeth (Canadian Journal of Speech-Language Pathology & Audiology)
Speech production is the result of a complex set of interactions between components of the language processing system. The longer the word, the greater the possibility for ‘error,’ because of interactions between word length, stress, CV sequences, consonants and vowels. Nonlinear phonological frameworks influenced by Optimality Theory and connectionist frameworks allow description of output at various levels of the phonological system and their interactions, and thus can help with interpretation of variable speech production patterns. The current paper provides a nonlinear analysis of one 8-year-old’s speech profile, which shows interactions between word structure and segments as word complexity increases. The participant has a rare metabolic condition: 3-methylglutaconic aciduria type I. To date, no reports have described speech profiles of children with this condition and thus, the paper also contributes to the literature on that condition.